2013
DOI: 10.12968/bjcn.2013.18.10.476
|View full text |Cite
|
Sign up to set email alerts
|

Improving efficiency and safety for patients who are unable to self-administer insulin

Abstract: A one-day 'snapshot' study was conducted to determine the nature and extent of specific safety issues faced by community nurses who care for patients unable to self-administer insulin. Community teams from 19 NHS trusts reported 607 patients requiring support with insulin administration. In total, 15.1% of insulin administration documents had an abbreviation for the word 'units', which is a serious safety hazard where any resulting serious harm would be classed as a 'never event'. Pens or disposable devices we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…54 When nursing assistants have been used effectively in relation to medication visits, they have been shown to improve access, reduce the pressure on qualified staff and have the potential to reduce costs. [29][30][31][32][33][34][35][36][37][38][39][40][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Despite the positive evidence for skill mix, a survey conducted by the RCN Eastern suggested that nearly half of the 139 respondents found that skill mix in their teams was insufficient to meet patient need. 49 However, the use of skill mix with nursing assistants working within tightly defined roles in the community could result in increased delivery of task-focused nursing care as, from a patient perspective, those with complex morbidities might experience more than one nurse from the same team calling to provide different aspects of care, with a detrimental impact on continuity of care and, therefore, on perceived quality.…”
Section: Workforce Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…54 When nursing assistants have been used effectively in relation to medication visits, they have been shown to improve access, reduce the pressure on qualified staff and have the potential to reduce costs. [29][30][31][32][33][34][35][36][37][38][39][40][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Despite the positive evidence for skill mix, a survey conducted by the RCN Eastern suggested that nearly half of the 139 respondents found that skill mix in their teams was insufficient to meet patient need. 49 However, the use of skill mix with nursing assistants working within tightly defined roles in the community could result in increased delivery of task-focused nursing care as, from a patient perspective, those with complex morbidities might experience more than one nurse from the same team calling to provide different aspects of care, with a detrimental impact on continuity of care and, therefore, on perceived quality.…”
Section: Workforce Issuesmentioning
confidence: 99%
“…A medication error involving insulin (much of which is administered by community nurses in patients' homes) would be designated a 'never event', as its impact on the patient could be catastrophic. 29 The duty of candour states that staff should be honest and transparent in their communications with patients and their relatives when things go wrong. 30 The contract also includes locally agreed incentive schemes and requires reporting on service quality issues, such as complaints, serious incidents, staff numbers and skill mix, all of which can provide a regular snapshot of real-time feedback on service quality.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, 20%–24% of people with type 2 diabetes are prescribed insulin (Sharma et al, 2016), and an estimated 18.8% in the United States (Pantalone et al, 2015). Modelling has suggested that UK community nurses administered insulin to an estimated 10,800 people with diabetes who could not do this themselves, due to a variety of issues, such as arthritis, or cognitive capacity (memory loss) (Livingstone et al, 2013). Furthermore, over 50% required multiple injections per day, comprising a significant proportion of the community nursing workload (Livingstone et al, 2013).…”
Section: Introductionmentioning
confidence: 99%